Auto- and allo-epitopes in DQ alloreactive antibodies. Issue 4 (August 2016) - Tambur, Anat R.
Abstract : Purpose of review: Significant interest is now focused on deciphering human leukocyte antigen (HLA) epitopes and the utilization of this new knowledge to improve donor–recipient matching in transplantation. A recently introduced concept is the appearance of antibodies against what may be considered as self-epitopes, including the introduction of the 'nonself–self paradigm'. Recent findings: Common practice in analyzing HLA-DQ antibodies have been to separate between antibodies against the α chain and antibodies against the β chain of the molecule. This is despite the fact that the two chains have to intertwine together to be expressed stably on the cell surface. We have previously provided evidence that this practice is false. We further provide evidence to refute the use of 'self-epitopes' as an immunologically feasible terminology by delineating the historic events leading to today's misconceptions. Summary: The evidence we present supports the need for a change in current practices. HLA-DQ antigens and antibodies should be viewed as combined DQα/β complexes. This will have impact to assigning cPRA value, assigning acceptable and unacceptable antigens, and pave the way to a better understanding of true HLA epitopes as we strive to improve donor–recipient compatibility and minimize generation of de-novo HLA antibodies.